The liquidity of bank assets and banking stability - Wagner, Wolf (Journal of Banking & Finance, 2007)
This paper shows that an increased liquidity of bank assets, paradoxically, increases banking instability and the externalities associated with banking failures. This is because even though higher asset liquidity directly benefits stability by encouraging banks to reduce the risks on their balance sheets and by facilitating the liquidation of assets in a crisis, it also makes crises less costly for banks. As a result, banks have an incentive to take on an amount of new risk that more than offsets the positive direct impact on stability.